Analysis Juridical to Convict Recidivists Who Get Assimilation In Time Covid-19 Pandemic - Aswandi Syarif; Muhammad Ilyas; Mursyid Mursyid (Manunggal Halim Jaya, 2022)
This study aims to determine the basis for the provision of assimilation policies during the Covid-19 pandemic and to find out the reasons for the prosecutors demand maximum punishment against recidivist defendants who received assimilation during the Covid-19 pandemic. This research uses normative research methods, covering primary and secondary legal materials. and tertiary, this research was conducted at the Makassar District Prosecutor's Office at the Makassar Port, with the legal materials obtained and analyzed using a statutory approach to obtain a systematic picture. The results of this study indicate the provision of assimilation and integration for prisoners and children through the Regulation of the Minister of Law and Human Rights Number 10 of 2020 and the Decree of the Minister of Law and Human Rights Number 19 / PK / 01/04 /2020, the basis for the provision of maximum demands by the prosecutor to recidivist convicts, namely the Attorney General's circular. Research recommendations If this policy is seen as a strategy to reduce the spread of Covid-19 in prisons, the government should not immediately abandon the rules that have been made for the safety of the surrounding community.